Scholastic children's thesaurus - Bollard, John K.; Reed, Mike, 1951- (New York : Scholastic Reference, 2006)
Contains over five hundred alphabetically arranged entries, each with a definition and one or more synonyms, and includes example sentences.
"New and updated"--Cover.
Includes index.
6.4
5-8
Keywords: English language -- Synonyms and antonyms -- Dictionaries, Juvenile; English language -- Synonyms and antonyms -- Dictionaries; English language -- Synonyms and antonyms -- Dictionaries